Factors that affect the e-government procurement trust in Indonesia - Nanang, Herlino; Durachman, Yusuf; Subchi, Imam; Misman, Ahmad F.; Zulkifli, Zahidah (IEEE, 2019)
These Procurement system has been applied widely throughout the world, especially in Indonesia, especially in the government sector. E-procurement becomes very important especially efficiency and cost savings for procurement of goods and services procurement as well as company. Based on the analysis of the success factors of e-procurement produces three things such as: supplier and contract management; end-user behavior and eprocurement business processes; and information infrastructure and e-procurement. The findings of this research can guide the various stages and implementation efforts as well as the company. Researchers adopted research models related to the model trust. The hope is a comprehensive finding of factors into the implementation of government procurement systems.